Analysis of Mode Shape due to Flow Induced Vibration in pipes as a function of Flow Pattern - Satria, Iman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Piping systems are very important in industry, especially in industries related to fluids such as oil and gas industries. Some disturbances in a production or distribution process often occur due to problems in the piping system. One of the serious problems in piping systems is the flow-induced vibration. This vibration problem if not handled properly will cause damage to the structure of the piping system and related components such as pumps or other fluid machines. In this study, the influence of fluid characteristics and the type of support on the vibration pattern (mode shape) will be investigated experimentally. Fluid characteristics are expressed in air and liquid fractions. Two types of pipe support are simply supported and clamped supported in detail investigated. The shape mode of the pipe vibration that occurs is measured as a function of fluid characteristics and support type. The measurement results are experimentally then compared with the results of simulations conducted with Finite Element Analysis. The results of this study indicate that clamped support makes the pipe vibrate with a higher frequency, while fluid flow with a higher liquid fraction provides a higher vibration level.